The Impact of Product Cues and Brand Attitude towards Purchase Intention of Automobiles - Noor Azmi Hashim; Osman Mohammad; Mahmod Sabri Haron (Journal of Business Management and Accounting, 2014)
The varying characteristics reflective of the actual diversity in how intentions are conducted have found that intentions are significantly better predictors of purchase behavior for existing products and durable than for non-durable products. These results are remarkable because, in practice, intentions are often used to predict sales for new non-durable products, and they are better predictors of behaviors over a short horizon. Branding is also important because it communicates a brand’s business proposition. The most successful visual expression of a brand is its core attributes, and a positive emotional relationship between the brand and its audience needs to be established. Building a local, regional, or national brand with a clearly defined and understood target audience is difficult and even more difficult when a global brand is at stake. Some global brands are strongly associated with their country of origin. In certain categories, this is part of the essence of the brand. Automobiles are the most notable example. The objective of this study is to understand the variables influencing consumers’ purchase intention related to automobiles. In particular, this study provides insight  into  the  perception  of  Malaysian  consumers  with  regards  to  their  purchase intention of a certain brand of automobiles.